Elizabeth Peyton : reading & writing - Peyton, Elizabeth, 1965-; Thomas, Rachael; Hancock, Caroline; Irish Museum of Modern Art (Kilmainham, Dublin, Ireland) (Milan ; New York City : Charta ; Dublin : Irish Museum of Modern Art, 2009)
Item contains chapters from books, poems and extracts from literature as well as plates of work by the artist.
Catalog of an exhibition held at the Irish Museum of Modern Art, Apr. 1-June 21, 2009.
Includes interview with the artist.
boek
Keywords: Peyton, Elizabeth